Implikatur Percakapan dalam Komunikasi Antarsiswa SMP Wahid Hasyim Sumberwudi Karanggeneng Lamongan - Saputra, Muhammad Naufal Abdy; Fahmi, Mohammad Tsalis (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2024)
This research is a qualitative descriptive study which aims to describe the forms of lingual conversational implicatures that appear in communication between students at SMP WAHID HASYIM Sumberwudi Karanggeneng Lamongan. The method used in this research is the observation and interview method. The results of this research show that there are three lingual forms found, namely the command lingual form, the news lingual form and the question sentence lingual form. In this regard, there are six types of conversational implicatures in this research. The six types of conversational implicatures are inviting to refuse, mocking, ordering, requesting, and informing of facts. It is hoped that the results of this research can be used as a basis for capturing the implied meaning that the speaker wants to convey to the speech partner.